ANALISIS DINAMIKA SEBARAN SPASIAL SEDIMENTASI MUARA SUNGAI CANTUNG MENGGUNAKAN CITRA LANDSAT MULTITEMPORAL - Zulaiha Zulaiha; Nurlina Nurlina; Ibrahim Sota (Jurnal Fisika FLUX, 2014)
ABSTRACT: Given the pivotal role played by the Cantung River for the supervision and management of the public good becomes important. Incoming sediment load can damage the uncontrolled flow conditions of the Cantung river and estuary. Observations of suspended sediment can take advantage of multitemporal Landsat imagery. This study uses Landsat satellite image data corrected 5TM March 5, 1992 data acquisition path/row 117/62, Landsat data acquisition 5TM 22 May 1997 path/row 117/62, Landsat data acquisition 5TM March 27, 2000 the path/row 117/62. Several stages in processing the image, that is the conversion of DN to reflectance values, cropping, water-not water secession, and the class divide sediment concentration by density slicing technique. Spatial distribution of suspended sediment in the estuary of the Cantung River Landsat image processing results 5TM March 5, 1992, Landsat 5TM May 22, 1997, and March 27, 2000 Landsat 5TM show distribution patterns of suspended sediment from the River Cantung the same direction, that is northeast. Sediment concentrations were detected in the Landsat image processing 5TM March 5, 1992 the largest-value 27,564096 mg/l and the smallest 14,886048 mg/l. Sediment concentrations were detected in the Landsat image processing 5TM May 22, 1997 the largest-value 121,476776 mg/l and the smallest 12,647415 mg/l. Sediment concentrations were detected in the Landsat image processing 5TM March 27, 2000 most valuable 159,256704 mg/l and the smallest 10,584161 mg/l. Getting away from the effect Cantung River estuary sediment concentration of river flow Cantung tends to get smaller. Changes in the distribution area of the sediments of March 5, 1992 until March 27, 2000 amounted to 450 m2/year. Keywords: Remote Sensing, Sedimentation, Landsat, Cantung River